Design of two-photon molecular tandem architectures for solar cells by ab initio theory1. Issue 5 (20th May 2015) - Ørnsø, Kristian B.; Garcia-Lastra, Juan M.; De La Torre, Gema; Himpsel, F. J.; Rubio, Angel; Thygesen, Kristian S.
<x xml:space="preserve">Abstract</x> We present new two-photon molecular architectures for photovoltaics where atomic precision can be obtained by synthetic chemistry.